Pengaruh Kualitas Pelayanan Dan Layanan Fintech Terhadap Kepuasan Nasabah Bank BTN Kc Medan - Ashilla, Fitriani; Anas, Amril; Lubis, Tina Muhardika Handayani; Sutedjo, Bambang; Lubis, Junaidi (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
In facing rapid technological developments and the increasing needs and expectations of customers, Bank BTN is required to continuously improve service quality while optimizing fintech-based services. These two aspects are essential factors that determine customer satisfaction in using banking services. High-quality service creates a positive experience for customers, while fintech services provide convenience, speed, and efficiency in conducting transactions. Therefore, this study was conducted to address the following research questions: (1) whether Service Quality has a significant effect on Customer Satisfaction, (2) whether Fintech Services have a significant effect on Customer Satisfaction, and (3) whether both variables simultaneously influence Customer Satisfaction at Bank BTN Medan Branch Office. This research employs a quantitative approach using a survey method. The sample consists of 100 respondents who are active customers of Bank BTN Medan Branch. The data were analyzed using multiple linear regression with the assistance of SPSS version 25.0. The results show that Service Quality has a positive and significant effect on Customer Satisfaction, indicating that better service quality leads to higher customer satisfaction. Additionally, Fintech Services also have a positive and significant effect on Customer Satisfaction, demonstrating that optimal utilization of digital services enhances customer comfort and satisfaction. Simultaneously, both variables significantly influence Customer Satisfaction. These findings provide theoretical contributions to the field of service marketing management and practical benefits for Bank BTN in improving service quality and digital innovation to maintain and strengthen customer loyalty.